Compact stars cooling and secular instability - Falcón, Nelson (Ciencia, 1970)
Compact stars cooling theory is revised thought secular stability criteria, this is when the relaxation times are not negligible. Using the Cattaneo Law for the heat flux, it is shown changes in the energy transport equation and insinuates quasiperiodic pulses in the luminosity. Applications in rapid variations in single white-dwarf oscillators and quasi periodic luminosity pulses of Neutron Stars (NS) are suggested. Also we discussed the Secular Stability in milliseconds emissions Pulsar.